The first co-opted endogenous foamy viruses and the evolutionary history of reptilian foamy viruses - Aiewsakun, P; Simmonds, P; Katzourakis, A (MDPI, 2019)
A recent study reported the discovery of an endogenous reptilian foamy virus (FV), termed ERV-Spuma-Spu, found in the genome of tuatara. Here, we report two novel reptilian foamy viruses also identified as endogenous FVs (EFVs) in the genomes of panther gecko (ERV-Spuma-Ppi) and Schlegel's Japanese gecko (ERV-Spuma-Gja). Their presence indicates that FVs are capable of infecting reptiles in addition to mammals, amphibians, and fish. Numerous copies of full length ERV-Spuma-Spu elements were found in the tuatara genome littered with in-frame stop codons and transposable elements, suggesting that they are indeed endogenous and are not functional. ERV-Spuma-Ppi and ERV-Spuma-Gja, on the other hand, consist solely of a foamy virus-like env gene. Examination of host flanking sequences revealed that they are orthologous, and despite being more than 96 million years old, their env reading frames are fully coding competent with evidence for strong purifying selection to maintain expression and for them likely being transcriptionally active. These make them the oldest EFVs discovered thus far and the first documented EFVs that may have been co-opted for potential cellular functions. Phylogenetic analyses revealed a complex virus-host co-evolutionary history and cross-species transmission routes of ancient FVs.